The Role of Technology Innovation in Enhancing Financial Reporting Quality in Digital Enterprises in Seychelles - Zelime, Elton (PT. Batari Edu Calya, 2026)
The rapid advancement of digital technologies has fundamentally transformed financial management practices across global enterprises, necessitating a comprehensive examination of how technology innovation influences financial reporting quality. This study investigates the role of technology innovation in enhancing financial reporting quality within digital enterprises operating in Seychelles, a jurisdiction increasingly positioning itself as a hub for digital business operations. Drawing upon theoretical frameworks of digital transformation and financial management innovation, this research synthesizes empirical evidence from multiple studies examining the intersection of digital finance, technological innovation, and enterprise financial performance. The analysis reveals that technology innovation, encompassing blockchain technology, artificial intelligence, cloud computing, and big data analytics, significantly improves the timeliness, security, reliability, and overall quality of financial reporting. Furthermore, the study identifies critical mediating mechanisms through which digital transformation enhances financial reporting, including the alleviation of financing constraints, optimization of resource allocation, and improvement of operational efficiency. The findings contribute to the theoretical understanding of digital transformation's impact on financial management while providing practical implications for digital enterprises in Seychelles seeking to leverage technology innovation for enhanced financial reporting quality.